The rough patch eaudiobook - Lies, Brian (2018)
A Caldecott Honor Book An ALA Notable Book A luminescent book that is pitch-perfect for anyone of any age who has experienced any type of loss or disappointment, from New York Times– bestselling picture book creator Brian Lies. New York Times–bestselling author Brian Lies has created a beautiful, accessible, and deeply personal story about friendship, loss, and renewal. The Rough Patch was awarded a Caldecott Honor. Evan and his dog do everything together, from eating ice cream to caring for their prize-winning garden, which grows big and beautiful. One day the unthinkable happens: Evan's dog dies. Heartbroken, Evan destroys the garden and everything in it. The ground becomes overgrown with prickly weeds and thorns, and Evan embraces the chaos. But beauty grows in the darkest of places, and when a twisting vine turns into an immense pumpkin, Evan is drawn out of his isolation and back to the county fair, where friendships—old and new—await. A deeply hopeful and positive book, The Rough Patch was awarded a Caldecott Honor and is a story about love, loss, and hope, and the healing power of friendship and nature. "Weepy and wonderful."—Wall Street Journal